Predicting infractions and health care utilization in prison: a meta-analysis - Gonçalves, Leonel C. (2014)
This meta-analysis was conducted to examine predictors of two indicators of inmates' adjustment to prison life: institutional infractions and health care utilization. Focusing on male prisoners, the final data set consisted of 90 studies and produced 1,815 correlations. Predictors were grouped into personal and contextual characteristics. Regarding institutional infractions, the strongest personal predictors were prior prison misconduct, aggressiveness, impulsiveness, antisocial traits, institutional risk, and younger age. At the contextual level, higher infraction rates were observed in prisons with more gang activity, and in prisons housing more inmates and a larger proportion of maximum security inmates. Major correlates of health care utilization were prior mental health problems, older age, and physical symptoms. Moderator effects were observed for prison sample size, sample selection, length of follow-up, geographic location, and type of analysis. These findings may help to improve prison classification procedures to optimize prisoners' management and treatment.